2008
DOI: 10.1088/1468-6996/9/4/044102
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and superconducting properties of CaC6

Abstract: Among the superconducting graphite intercalation compounds, CaC 6 exhibits the highest critical temperature T c = 11.5 K. Bulk samples of CaC 6 are obtained by immersing highly oriented pyrographite pieces in a well-chosen liquid Li-Ca alloy for 10 days at 350• C. The crystal structure of CaC 6 belongs to the R3m space group. In order to study the superconducting properties of CaC 6 , magnetisation was measured as a function of temperature and direction of magnetic field applied parallel or perpendicular to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
36
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 51 publications
6
36
0
5
Order By: Relevance
“…1). An excellent review has been published recently [51], which would make redundant an overview of the growth, structure and superconductivity in this section. We shall, however, fill a gap in that review and compare superconducting transition temperatures in metal-intercalated fullerite and graphite (see Fig.…”
Section: Graphite and Fullerite Intercalated With Alkali Metalsmentioning
confidence: 99%
“…1). An excellent review has been published recently [51], which would make redundant an overview of the growth, structure and superconductivity in this section. We shall, however, fill a gap in that review and compare superconducting transition temperatures in metal-intercalated fullerite and graphite (see Fig.…”
Section: Graphite and Fullerite Intercalated With Alkali Metalsmentioning
confidence: 99%
“…The highest T = 11.5 K was obtained for relatively large calcium [83] and therefore, we may hope to see a further increase for lighter elements.…”
Section: Carbon Nanotubes Metalintercalated Graphite and Fulleritesmentioning
confidence: 84%
“…An excellent review has been published a few months ago [83], virtually obliterating this section. We [73,81,84] and graphites [83] plotted vs. the radius of the metal ion A + (bottom panel).…”
Section: Carbon Nanotubes Metalintercalated Graphite and Fulleritesmentioning
confidence: 99%
“…Therefore their doping has been attempted in order to achieve high-transition-temperature superconductivity. In fact, several studies have revealed superconductivity in carrier-doped carbon materials, such as intercalated graphite compounds [1][2][3] and fullerene compounds [4][5][6], where carrier doping is realized via alkali-metal or alkaline-earth-metal doping. In the case of diamond, superconductivity has been realized by boron doping [7].…”
Section: Introductionmentioning
confidence: 99%